QOLP-12. A NOVEL MULTIDISCIPLINARY CARE CLINIC MODEL FOR FRAIL PATIENTS WITH CENTRAL NERVOUS SYSTEM MALIGNANCIES. (5th November 2018) - Nevel, Kathryn; Elizabeth Davis, Mary; Skakodub, Anna; Ali, Jessica; Sullivan-Henry, Anne; Gilman, Jodi; Harrison, Mabel; Huang, Melody; Bailey, Lauren; Mack, Kyle; Rawlins-Peters, Gayle; Jean-Charles, Dominique; et al.
Abstract: BACKGROUND: Physical, cognitive, and existential needs are common in patients with central nervous system (CNS) malignancies, however not all needs can be addressed in routine clinic visits. To identify and address complex patient and caregiver needs, we implemented a novel multidisciplinary care clinic (MDCC) for patients with CNS malignancies at our institution. METHODS: Monthly between 8/2017-4/2018, a team comprising a neurologist, physiatrist, nurse, physical therapist, case manager, social worker, dietitian and chaplain assessed patients with CNS malignancies, neurological deficits and KPS ≤80. Within a 3 hour-visit, providers rotated in to see patient/caregiver. Starting in 11/2017, participants completed validated surveys on unmet needs, financial strain, and home equipment prior to MDCC and on satisfaction after clinic. Descriptive statistics were used to analyze results. RESULTS: Forty-two patients were seen: twenty-two (50%) were female; median age=64. Diagnoses included gliomas (n=30), brain metastases (n=8), other primary brain tumors (n=4); median KPS=70 (range 50–80). Thirty-one (74%) patients were on cancer-directed therapy and eleven (26%) on surveillance. Twenty-five patients completed pre-MDCC surveys, the predominant unmet need (96%) was: "not being able to do the things you used to do"; 15 (60%) expressed worry about their ability to pay for cancer care. Twenty-four caregivers completed the pre-MDCC survey, the predominant unmet need (83%) was: "I need my partner to have an ongoing case manager." At MDCC, 38 (90%) patients received recommendations for symptom management, 34 (81%) discussed prognosis and/or coping with cancer, and 33 (78%) established or updated their physical therapy and/or home services. Twenty-four patients (57%) completed a post-MDCC satisfaction survey: 100% felt the clinic was helpful, and 96% would recommend the clinic to others. CONCLUSION: This study identifies a new shared-appointment model of care to identify and address unmet needs. Additional prospective study is needed to determine the role of this clinic in neuro-oncologic care.